THE EFFECT OF HOOKAH (SHISA) AND VAPING ON CARDIOVASCULAR DISEASE: A LITERATURE REVIEW: Pengaruh Hookah (Shisha) dan Vaping Pada Penyakit Kardiovaskular: Tinjauan Pustaka - Haroon, Aqsa; Atoillah Isfandiari, Muhammad; Umbul Wahyuni, Chatarina (Universitas Airlangga, 2024)
Background: The popularity of shisha (hookah) and vaping as alternatives to smoking has increased significantly in recent years. Shisha smoking, prevalent in Arab nations and other regions, exposes users to various harmful substances including nicotine, fine particles, carbon monoxide, polycyclic aromatic hydrocarbons, and heavy metals. Similarly, vaping involves inhaling aerosols produced by heating e-liquids containing nicotine and other chemicals. Purpose: This literature review aims to provide a comprehensive summary of recent studies examining the cardiovascular health effects of shisha and vaping. Methods: Epidemiological patterns and adverse consequences of these practices on cardiovascular health were explored through a systematic search of relevant articles from PubMed, ScienceDirect and Google Scholars. Results: The findings suggest that chronic use of shisha and vaping is associated with respiratory issues and adverse cardiovascular outcomes. Moreover, shisha smoking has been linked to infectious diseases, pulmonary complications, metabolic syndrome, and adverse effects on fetal development during pregnancy. Conclusion: The review highlights the need for further research to better understand the mechanisms and long-term cardiovascular consequences of shisha and vaping.